Safety of red yeast rice supplementation: A systematic review and meta-analysis of randomized controlled trials - Fogacci, Federica; Banach, Maciej; Mikhailidis, Dimitri P; Bruckert, Eric; Toth, Peter P; Watts, Gerald F; Reiner, Željko; Mancini, G. B. John; Rizzo, Manfredi; Mitchenko, Olena; Pella, Daniel; Fras, Zlatko; et al. (Pharmacological research, 2019)
Recently, concerns regarding the safety of red yeast rice (RYR) have been raised after the publication of some case reports claiming toxicity. Since the previous meta-analyses on the effects of RYR were mainly focused on its efficacy to improve lipid profile and other cardiovascular parameters, we carried out a meta-analysis on safety data derived from the available randomized controlled clinical trials (RCTs). Primary outcomes were musculoskeletal disorders (MuD). Secondary outcomes were non-musculoskeletal adverse events (Non-MuD) and serious adverse events (SAE). Subgroups analyses were carried out considering the intervention (RYR alone or in association with other nutraceutical compounds), monacolin K administered daily dose (≤3, 3.1-5 or >5 mg/day), follow-up (>12 or ≤12 weeks), with statin therapy or statin-intolerance and type of control treatment (placebo or statin treatment). Data were pooled from 53 RCTs comprising 112 treatment arms, which included 8535 subjects, with 4437 in the RYR arm and 4303 in the control one. Monacolin K administration was not associated with increased risk of MuD (odds ratio (OR) = 0.94, 95% confidence interval (CI) 0.53,1.65). Moreover, we showed reduced risk of Non-MuD (OR = 0.59, 95%CI 0.50, 0.69) and SAE (OR = 0.54, 95%CI 0.46, 0.64) vs. control. Subgroups analyses confirmed the high tolerability profile of RYR. Furthermore, increasing daily doses of monacolin K were negatively associated with increasing risk of Non-MuD (slope: -0.10; 95%CI: -0.17, -0.03; two-tailed p < 0.01). Based on our data, RYR use as lipid-lowering dietary supplement seems to be overall tolerable and safe in a large kind of moderately hypercolesterolaemic subjects.
Keywords: Dietary Supplements; Musculoskeletal Diseases; Biological Products; biologické přípravky; Humans; lidé; Randomized Controlled Trials as Topic; muskuloskeletální nemoci; randomizované kontrolované studie jako téma; potravní doplňky